Selective Triazenation Reaction (STaR) of Secondary Amines for Tagging Monomethyl Lysine Post‐Translational Modifications. (24th February 2021) - Nwajiobi, Ogonna; Mahesh, Sriram; Streety, Xavier; Raj, Monika
Abstract: Lysine monomethylation (Kme) is an impactful post‐translational modification (PTM) responsible for regulating biological processes and implicated in diseases, thus there is great interest in identifying these methylation marks globally. However, the progress in this area has been challenging because the addition of a small methyl group on lysine leads to negligible change in the bulk, charge, and hydrophobicity. Herein, we report an empowering chemical technology selective triazenation reaction, which we term "STaR", of secondary amines using arene diazonium salts to achieve highly selective, rapid, and robust tagging of Kme peptides from a complex mixture under biocompatible conditions. Although the resulting triazene‐linkage with Kme is stable, we highlight the efficient decoupling of the triazene‐conjugate to afford unmodified starting components under mild conditions when desired. Our work establishes a unique chemoselective, traceless bioconjugation strategy for the selective enrichment of Kme PTMs. Abstract : We report a novel chemoselective s elective t ria zenation r eaction, termed „STaR", of secondary amines for the selective enrichment of monomethyl lysine (Kme) post‐translational modifications from a complex protein mixture using diazonium ions under physiological conditions followed by the „traceless" release of the Kme peptides under mild acidic conditions.